Defective production of interferon-γ and tumour necrosis factor-α by AIDS mononuclear cells after in vitro exposure to Rhodococcus equi - S. Delia; C. M. Mastroianni; M. Lichtner; F. Mengoni; S. Moretti; V. Vullo (Mediators of Inflammation)
The production of interferon-γ and tumour necrosis factor-α was evaluated in the peripheral blood mononuclear cells (PBMCs) from healthy donors and AIDS patients after Rhodococcus equi infection in vitro. PBMCs from healthy donors secreted elevated levels of IFN-γ and TNF-α when challenged in vitro with killed R. equi, whereas the release of both cytokines was impaired in supernatant cultures from AIDS patients. We conclude that the failure of IFN-γ generation in AIDS patients in response to R. equi is not antigen-specific but it may reflect the global impairment of T-cell function. In such patients, however, the infection with R. equi, a facultative intracellular pathogen which survives and replicates within macrophages, may be responsible for the impairment in the TNF-α release, possibly enhancing the HIV-induced macrophage dysftmction.